Injectable “Skin Boosters” in Aging Skin Rejuvenation: A Current Overview - Nark-Kyoung Rho; Hyun-Seok Kim; Soo-Young Kim; Won Lee (Archives of Plastic Surgery)
Aging-related changes in the skin, such as dullness, dehydration, and loss of elasticity, significantly affect its appearance and integrity. Injectable “skin boosters,” comprising various biological materials, have become increasingly prominent in addressing these issues, offering rejuvenation and revitalization. This review offers a comprehensive examination of these injectables, detailing their types, mechanisms of action, and clinical uses. It also evaluates the evidence for their effectiveness and safety in treating age-related skin alterations and other conditions. The goal is to provide an insightful understanding of injectable skin boosters in contemporary dermatological practice, summarizing the current state of knowledge.